Evaluating Of Effectiveness Of Green Promotion In Formation Consumers Attitudes Towards Green Products (A Survey Study In Medication Consumers In Lattakia City) - الخير عبير; بسام زاهر; ريزان نصور (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to study the role of green promotion tools represented in (Green packaging, Advertisement, Eco Labels) in shaping consumers’ attitudes towards green products in the city of Lattakia. After the great increase in awareness about various environmental problems, which led to a change in consumer attitudes and purchasing behavior, and most of them turned to environmentally friendly products, many companies sought to include green promotion within their promotional policies, especially since it constitutes a vital source of information for them, which contributes to shaping and changing their attitudes towards environmentally friendly products. Where the descriptive analytical approach was adopted to collect secondary data through Arabic and foreign books and references, articles and periodicals issued in the field of research. The researcher adopted the statistical method, and the preliminary data were collected through a questionnaire form as a tool for study, which was organized based on the researcher’s knowledge of published literature, questionnaire was distributed to a sample of research that represented by 400 consumers. In order to test hypotheses, the researcher unloaded a database using SPSS issue 23 and adopted on Alpha Crompbach to measure the stability of the meter. The main result of the research was no existence of a fundamental role for green Promotion tools represented in (Green packaging, Advertisement, Eco Labels) in Formation Consumers Attitudes towards Green Products